An international online collaborative learning project for occupational therapy students: A mixed-methods study. - Jasem, Zainab A.; Lister, Helga Elke; Kharva, Nabeela; Tellers, Susanne; Burgess, Sian; Kollmann, Stefan; McGinley, Sarah L.; Buys, Tania Lee; Jarrey, Mike (Scandinavian Journal of Occupational Therapy, 2025)
Background: Internationalization-at-home facilitates intercultural learning and cultivates global citizenship opportunities for students in higher education while in their home environments. The International Discussions in Occupational Therapy (i-DOT) project is an annual, online collaborative learning initiative that supports occupational therapy education. Aim: This study aims to assess the benefits of the i-DOT project and identify factors influencing student participation. Material and methods: A convergent mixed methods design was used. Quantitative survey data and qualitative focus groups and/interviews were gathered from occupational therapy students and educators involved in the project. Results: Data were collected from 139 students who completed an online questionnaire and 14 students and educators who participated in the focus groups or interviews. Reported benefits included improved social and interpersonal skills, professional, and academic development, and increased diversity awareness. Most students indicated that these outcomes would not have been achieved through engagement with peers from their own country alone. Challenges to participation were attributed to logistical issues and participant-related difficulties. Conclusion and significance: Participation in the i-DOT project enabled equitable international engagement for occupational therapy students. Despite participation barriers, occupational therapy students enhanced their learning and developed skills essential for independent professional practice.